International Handbook on Gender and Demographic Processes (International Handbooks of Population, 2018)
This handbook presents a comprehensive and up-to-date overview of gender in demography, addressing the many different influences of gender that arise from or influence demographic processes. It collects in one volume the key issues and perspectives in this area, whereby demography is broadly defined. The purpose in casting a wide net is to cover the range of work being done within demography, but at the same time to open up our perspectives to neighboring fields to encourage better conversations around these issues. The chapters in this handbook carefully document definition and measurement issues, and take up parts of the demographic picture and focus on how gender plays a role in outcomes. In other cases, gender often plays a cross-cutting role in social processes; rather than having a single or easily distinguishable role, it often combines with other social institutions and even other statuses and inequalities to affect outcomes. Thus, a key factor in this volume is how gender interacts with race/ethnicity, class, nationality, and sexuality in any demographic setting. While each section contains chapters that are broad overviews of the current state of knowledge and behavior, the handbook also includes chapters that focus on specific cultures or events in order to examine how gender operates in a particular circumstance. .